Pharyngolaryngeal reflux disease - Can symptoms predict endoscopic findings? - Costa, Isabel (2021)
Aim: to correlate the severity of symptoms with pharyngolaryngeal endoscopic findings in individuals diagnosed with pharyngolaryngeal reflux disease (PLRD). Design of the study: unicentric, observational and prospective study. Material and Methods: 109 adults attended the ENT and Gastroenterology consultation at Hospital de Braga between April and October 2019 with suspected symptoms of PLRD. Through the application of two questionnaires - the Reflux Symptom Index (RSI) and the Reflux Finding Score (RFS) – a final sample of 39 patients was obtained. All individuals were also submitted to upper digestive endoscopy and esophageal pH impedance. Results: The most frequent symptom was throat clearing (3,64). The average RSI score was 23.4±9.1. The laryngoscopic findings that most correlated with the presence of symptoms (namely dysphonia) were erythema/hyperemia ((p=.036) and the presence of ventricular obliteration (p=.015). The diagnosis of GERD was confirmed in 13 patients (33%). Cough after lying down was the only symptom that was associated with a higher incidence of GERD (p=.01). Conclusions: The authors concluded that there is a correlation between some findings at laryngoscopy and symptoms of PLR.